Knowledge And Attitude on Strabismus of Parents wiith Strabismic Children - Tripathi, Bishal Mani; Bhusal, Usha (Journal of Interdisciplinary Studies, 2025)
Strabismus is a common pediatric ocular condition that affects binocular vision and is associated with significant psychosocial consequences. In developing countries such as Nepal, delayed diagnosis and treatment are frequently attributed to poor parental awareness and prevalent cultural misconceptions. Assessing parental knowledge and attitudes is therefore crucial for improving early intervention and visual outcomes. This descriptive cross-sectional study was conducted from December 2023 to December 2024 at Lumbini Eye Institute & Research Center (LEIRC), Rupandehi, Nepal, to evaluate the knowledge and attitudes of parents of children with strabismus. A total of 143 parents of children aged 1–16 years were recruited using convenience sampling. Data were collected using a pretested, structured questionnaire consisting of six knowledge-based and seven attitude-based items. Knowledge scores ≥4 were categorized as “good knowledge,” and attitude scores ≥5 were considered a “positive attitude.” Data were analyzed using SPSS version 22. Findings showed that only 29.4% of respondents had good knowledge, whereas 61.5% demonstrated a positive attitude toward strabismus. Most parents recognized strabismus as a treatable condition (95.1%) and perceived it as a cosmetic concern (73.4%). Spectacles were the most commonly identifi ed treatment option (64.3%). No statistically significant association was found between knowledge and attitude (p = 0.486). In conclusion, although parental knowledge regarding strabismus was limited, attitudes were generally positive. This may reflect strong cultural values related to family care and growing trust in institutional eye care services. Community-based health education and school health programs could play a crucial role in enhancing early detection and timely management of strabismus in Nepal.